SIKAP KELOMPOK TANI TERHADAP GERAKAN NASIONAL KAKAO DI KABUPATEN BOLAANG MONGONDOW UTARA - Yesitha J. Lomban; Lyndon R.J. Pangemanan; Jenny ., Baroleh (Sam Ratulangi University, 2017)
This study aims to examine the attitude of farmer groups to Gernas Kakao in Bolaang Mongondow Utara District. The study lasted for three months from April to June 2017 in Bolaang Mongondow Utara District. The data used are primary data collected through interviews with 5 farmer groups taken by purposive sampling ie 3 groups of advanced farmers and 2 groups of farmers beginners class. Each farmer group was taken by 6 people consisting of farmer group members such as chairman, secretary, treasurer and 3 members so that the total of 30 respondents. Secondary data were obtained from the Office of Agriculture and District Office in Bolaang Mongondow Utara. The method of analysis used is descriptive. The results showed that farmers' attitudes in cocoa farmer groups at both beginner and advanced level of Cocoa Gernas Program in intensification, rejuvenation and rehabilitation activities were categorized as high in the sense strongly agreed that this program increased cocoa production. However. there are still farmers who disagree with this program because they rarely follow the counseling and guidance of the companion so that their knowledge, attitudes and behavior are different from other farmers who actively participate in the Cocoa Gernas Program. Farmers are still afraid of the risk of failure in production so that they can not accept the new technologies given and prefer to cultivate the plants in their own way, this happens to the beginner farmer groups so that the necessary extension workers and companions to change the mindset of farmers.